On-Water Synthesis of Dipyrromethanes via Bis-Hetero-Diels–Alder Reaction of Azo- and Nitrosoalkenes with Pyrrole - Pereira, Nelson A. M.; Lopes, Susana M. M.; Lemos, Américo; Pinho e Melo, Teresa M. V. D. (Synlett, 2014)
An unprecedented one-pot approach to 5-substituted dipyrromethanes based on the hetero-Diels–Alder reaction of azo- and nitrosoalkenes is described. The on-water reaction conditions led to the target compounds in higher yields with significantly shorter reaction times and simpler purification procedures than carrying out the reaction in dichloromethane or in the absence of solvent.
Keywords: dipyrromethane; Diels–Alder reactions; on-water reactions; azoalkenes; nitrosoalkenes